The Effect of Cacao Leaf Extract as An Inhibitor with A Concentration Variation of 0%, 3%, 5%, And 7% on The Corrosion Rate of St 37 Steel with Immersion Time of 3 Days And 6 Days in NaCl Corrosive Medium 3% - Nia Diana; Ediman Ginting; Pulung Karo Karo (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
This study aims to determine the effect of adding inhibitors of cacao leaf extract with concentrations of 0%, 3%, 5%, and 7% in 3% NaCl corrosive medium on the corrosion rate of St 37 steel, knowing the effect of cacao leaf extract in inhibiting the corrosion rate of St 37 steel in NaCl solution and knowing the microstructure, phase, and corrosion products on St 37 steel after immersion in NaCl solution. The weight loss method was carried out to determine the value of the resulting corrosion rate. The Fourier transform infrared (FTIR) analysis showed the presence of tannins in the cacao leaf extract. The X-ray Diffraction (XRD) result shows that the formed phase is pure Fe. It is reinforced by the Energy Dispersive Spectroscopy (EDS) result, which shows that the more lumps on the steel surface, the fewer Fe elements, and the more FeO corrosion product. Scanning Electron Microscopy (SEM) results show the presence of lumps of various sizes and black holes resulting from corrosion.